Anticipated Stigma and Defensive Individualism During Postincarceration Job Searching*. Issue 3 (11th June 2016) - Ray, Bradley; Grommon, Eric; Rydberg, Jason
Abstract : Obtaining employment is one of the most difficult challenges for individuals released from prison. This research explores the strategies recently released male parolees employ in attempting to find work, with specific attention to the role of anticipated stigma from their ex‐convict status. Through the use of in‐depth longitudinal interviews, this research contributes to our understanding of returning prisoner's experiences in job searching. We find that although a majority of the sample anticipated stigma as a barrier to employment, those who did expressed an extreme self‐reliance consistent with defensive individualism. This reluctance to draw on social networks may ultimately be counter‐productive to the search for employment.